Do non‐maternal adult female household members influence child nutrition? Empirical evidence from Ethiopia. (9th July 2021) - Usman, Muhammed Abdella; Kornher, Lukas; Sakketa, Tekalign Gutu
Abstract: Child malnutrition is an enormous public health problem in low‐ and middle‐income countries (LMICs). In this paper, we study the relationship between non‐maternal adult female household members (AFHMs) and under‐5 child nutritional outcomes using nationally representative Ethiopian Demographic and Health Survey data, 2016. Because most of the primary inputs that go into the production of child health are intensive in maternal time, having additional AFHMs may ease the time constraints of the child's mother. We use anthropometric measures such as height‐for‐age z ‐scores (HAZ) and weight‐for‐age z ‐scores (WAZ) to measure stunting and underweight, respectively, as objective indicators of child nutritional status. Among our sampled households, we find that 40% of the children are stunted, 18% severely stunted, 27% underweight and 8% severely underweight. Furthermore, about 20% of the sampled children live with at least one extra non‐maternal AFHM. The multivariate regression results suggest that an additional AFHM is associated with significantly higher HAZ and WAZ scores and less likelihood of severe stunting compared with children living with fewer AFHMs. Finally, the paper discusses the potential pathways through which non‐maternal AFHMs can influence child nutritional status. Abstract :